SOCIO-DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF TURKISH WORKERS WITH PNEUMOCONIOSIS - Altinoz, Hilal; Celikkalkan, Cengiz; Horasan, Gonul Dinc; Hamsioglu, Fatih; Cengiz, Nalan; Orbay, Hikmet (NATL INST PUBLIC HEALTH, 2016)
Aim: Pneumoconiosis is caused by inhaling dust. The aim of the study was to analyze 208 cases of workers' pneumoconiosis. Method: Patients' files were used for the descriptive study. Results: All patients were male aged 38.82 +/- 13 years. The most important symptom was breathlessness. Patients were denim sandblasters (50.5\%), dental technicians (12\%), coal miners (6.7\%), and others. The mean exposure time before pneumoconiosis occurred was shorter in denim sandblasters and teflon kitchenware producers compared to other occupations (5.4 +/- 4.2 and 4.5 +/- 3.3 years, respectively). Profusion (76.5\%) was more than 1/2 by the International Labour Organization (ILO) classification. Pulmonary function tests were negatively correlated with profusion. Conclusion: Denim sandblasters and teflon kitchenware producers have less exposure time before pneumoconiosis occurs and they become symptomatic earlier. As Turkish workers suffering from pneumoconiosis are younger, measures to prevent pneumoconiosis must be the priority of the healthcare authorities.
Keywords: pneumoconiosis; denim sandblasters; Turkish workers; dental technicians